2018
DOI: 10.3389/fpsyt.2018.00108
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Semantic Inhibition in Relation to Hypomanic Traits: An fMRI Study

Abstract: ObjectivesLanguage modifications are a core feature of mania, but little is known about the semantic mechanisms behind these disturbances. The aim of the present study was thus to identify deficits in semantic inhibition and their respective neural activation patterns in a sample of individuals assessed for hypomanic personality traits.MethodsThirty-six young adults with no neurological or psychiatric diagnoses were assessed for hypomanic personality traits with the Hypomanic Personality Scale (HPS) and underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Previous studies showed that controlled processes are impaired in a population vulnerable to BD ( Raucher-Chéné et al, 2017 , 2018 ). Our study shows that, in addition to an alteration in these controlled processes, the automatic process of spreading activation is also less efficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that controlled processes are impaired in a population vulnerable to BD ( Raucher-Chéné et al, 2017 , 2018 ). Our study shows that, in addition to an alteration in these controlled processes, the automatic process of spreading activation is also less efficient.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only two studies had explored semantic processes in a population vulnerable to BD. Both studies found abnormalities affecting semantic inhibition processing ( Raucher-Chéné et al, 2017 , 2018 ), that is controlled processes. Thus, semantic memory for controlled processes seems to be impaired in hypomanic individuals, but nothing is known about automatic semantic spreading activation in vulnerable populations.…”
Section: Introductionmentioning
confidence: 93%